1334 Improving Patient Flow Through the Hand Trauma Pathway. (12th October 2021) - Rela, M; Clough, E; Chu, H; Hughes, J
Abstract: Aim: A full-cycle audit was conducted at our plastic surgery unit, assessing adherence to hand trauma standards by the British Society for Surgery of the Hand. These stipulate that time from referral to clinic for open injuries and closed fractures should be within 24 hours and 72 hours respectively and time to theatre from date of injury (DOI) within 4 and 7 days, respectively. Method: Data for the initial audit was collected from Nov 2019-Feb 2020 and for the re-audit from Aug-Dec 2020. Lists were generated of 50 patients with open injuries including flexor tendon, extensor tendon and nerve injuries and 50 hand fractures in both cycles. Data was collected on DOI, date of referral, clinic review and surgery. Results: The initial audit results showed poor DOI documentation (open injuries 30%, fractures 54%). For open injuries, 44% met standards for clinical review within 24 hours and 94% for time to theatre. For fractures, 94% met the standard for time to clinic and 90% for time to theatre. The interventions included adding the standards to the clinic booking form and creating a mandatory DOI field on the referral system. The re-audit showed improvement of DOI documentation (open injuries 95%, fractures 100%) and the proportion of open injuries seen within 24 hours to 60%. Conclusions: The interventions had a positive impact on our hand trauma pathway. Areas for improvement include reducing the number of patient visits to the service and encouraging early decision-making, particularly for patients reviewed in the emergency department.